¿“Ex Gotorum Principis progenie ortus”? (Re)constructing the genealogy of kings at the early 13th century: The examples of Rodrigo Jiménez de Rada and Lucas of Tuy (History Journal «Jerónimo Zurita», 2024)
The aim of this article is to analyse the genealogical context in the texts of two chroniclers of the first half of the 13th century in Castile-León, Rodrigo Jiménez de Rada and Lucas of Tuy. Employed as an ideological tool and the vehicle for the legitimating exaltation of royal power, Latin historiography in Castile-León during the Middle Ages has to deal, when facing the past, with multiple discursive issues. A long and usually complex genealogy was, no doubt, one of the most important, and the different solutions adopted to solve the “problems” are the guiding lines of this research.
Keywords: Castile-León; 13th century; chronicles; kingship; ideology; history